Sub-concussive impacts and the menstrual cycle: A study of elite female footballers - Lowery, M.; Ronca, F.; Bruinvels, G.; Jones, C.; Loosemore, M.; Burgess, P. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Sub-concussive head impacts, particularly those incurred through sports like football, have been associated with long-term neurological risks. While repetitive sub-concussive head impacts have been extensively studied in male athletes, there is a dearth of research focusing on female athletes, despite evidence suggesting potential differences in susceptibility to sports-related concussion and symptom severity across menstrual cycle phases, particularly in the luteal phase. This study investigates whether menstrual cycle phases, influence head impact kinematics during sub-concussive impacts in elite female footballers. METHODS: Five naturally menstruating elite female footballers (mean age = 23 ± 4 years; mean stature = 163.5 ± 5.5 cm; mean body mass = 62.4 ± 6.2 kg) participated in a 16-week study. Menstrual cycle phases were tracked using the FitrWoman app alongside urinary ovulation kits. From weeks 4 to 16, participants performed a weekly controlled drill involving ten headers thrown from a 5m distance, with head accelerations measured using custom-fitted PROTECHT instrumented mouthguards. A linear mixed model was used to analyze differences in individual head impact acceleration across 256 separate heading events, with the menstrual cycle phase (menstruation, late follicular, ovulation, luteal, pre-menstrual) as the fixed effect and player as a random effect. RESULTS: The analysis revealed an average heading intensity of 17.5 ± 5.4 g (linear acceleration) and 1479 ± 548 rad.s-2 (rotational acceleration). At the group level, no significant differences were observed in peak linear (P = 0.357) or rotational accelerations (P = 0.752) from headers across menstrual cycle phases. However, at the individual level, two athletes experienced significantly greater head accelerations. One athlete had higher linear and rotational acceleration in the late follicular versus luteal phase (P = 0.023 and 0.050, respectively). Another showed increased linear acceleration in the pre-menstrual phase compared to late follicular (P = 0.006), and greater rotational acceleration in menstruation versus late follicular (P = 0.039). Descriptively, headers in the luteal phase exposed athletes to the lowest accelerations. CONCLUSION: Results suggest that hormonal fluctuations may not substantially influence head impact biomechanics among elite female athletes under controlled conditions. Although overall head acceleration may not vary with the menstrual cycle phase on average, individual athletes may still experience hormonal fluctuations that affect their head accelerations. While the findings are intriguing, the small sample size limits the generalizability of the results. Future research with larger cohorts and the inclusion of match-specific heading is warranted.